Antimicrobial potential of ethanol extracts of plants against gramnegative bacilli isolated from cervicovaginal mucosa of sheep bred in the region of Petrolina-PE - Silva, Valdenice Félix da; Franco, Isabelle; Damasceno, Tácito Emanuel Ferreira; Almeida, Jackson Roberto Guedes da Silva; Costa, Mateus Matiuzzi da (Semina: Ciências Agrárias, 2014)
Reproductive tract infections are the main causes of losses from the low reproductive efficiency of sheep. Gram negative bacilli belonging to the normal flora of the genital region can trigger diseases. The pathogenicity of these agents is expressed when females are with weakened immune system, either by food or stress management. Flaws in and concern about antibiotic residues in animal production have prompted research regarding alternatives for the treatment of diseases. The herbal medicine hás been considered in this context is the subject of numerous studies. This study aimed to evaluate the antibacterial potential of ethanol extracts of plants belonging to the flora of the Northeast against gram negative bacilli isolated from cervical-vaginal mucosa of sheep. Six plants were selected from Caatinga biome: Encholirium spectabile, Bromelia laciniosa, Neoglaziovia variegata, Amburana cearensis Hymenaea martiana and Selaginella convoluta. The plant material was processed to obtain the crude extract. This was tested by microdilution plate and determining the minimum bactericidal concentration, the second document of Clinical and Laboratory Standards Institute (CLSI) and the extracts diluted in water and alcohol. We used 43 gram negative isolates, as follows: 14 E. coli, 10 Enterobacter spp., 10 Acinetobacter spp. 9 and Klebsiella spp. In the aqueous dilution Klebsiella spp. showed response only to species B. laciniosa, S. convoluta and H. martiana. All tested extracts showed antibacterial activity against Acinetobacter spp and no activity against E. coli and Enterobacter spp. Among the extracts diluted in water H. martiana showed the highest antibacterial activity. In all dilution alcoholic extracts showed inhibitory activity against all bacterial genera, but no statistical difference between them.